2021
DOI: 10.5902/1983465944075
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the influence of intangible assets on the performance of Brazilian companies

Abstract: Purpose – The study aims to analyze the relationship between intangible assets and the economic performance of Brazilian public companies. Design/methodology/approach – We calculated the Degree of Intangibility (DI) to segregate companies into two groups: intangible-intensive and tangible-intensive in a sample of Brazilian public companies from 2012 to 2016. We applied the Mann-Whitney test to verify whether there were statistically significant differences between these two groups of companies concerning the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Intangible assets are viewed as one of the key success factors that help a company maintain its competitive advantage; thus, the current trends in the market motivate entities to realize to the benefits of acquiring such assets (Seo & Kim, 2020). de Almeida Aguiar, Tortoli, Figari, and Junior (2021) affirmed in their findings that intangibles inspire businesses to perform more economically, as appeared in the majority of performance metrics; such results provide credence to the premise that intangible assets have a significant and beneficial impact on dividends. Similarly, Mohanlingam, Nguyen, and Mom (2021) found that entities that hold greater amounts of intangible assets tend to pay more dividends.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Intangible assets are viewed as one of the key success factors that help a company maintain its competitive advantage; thus, the current trends in the market motivate entities to realize to the benefits of acquiring such assets (Seo & Kim, 2020). de Almeida Aguiar, Tortoli, Figari, and Junior (2021) affirmed in their findings that intangibles inspire businesses to perform more economically, as appeared in the majority of performance metrics; such results provide credence to the premise that intangible assets have a significant and beneficial impact on dividends. Similarly, Mohanlingam, Nguyen, and Mom (2021) found that entities that hold greater amounts of intangible assets tend to pay more dividends.…”
Section: Literature Reviewmentioning
confidence: 86%
“…We have also considered the main financial figures relating to these companies defined by market capitalization, net profit, sales, EBITDA (Earnings before interest, taxes, depreciation, and amortisation), price-to-book value, total assets, total tangible assets, total debt and total equity. Theses variables have been considered useful for this kind of study in similar works [11][12][13][14][15][16][17][18][19].…”
Section: Methodsmentioning
confidence: 99%
“…Portanto, quanto maior o NI, maior será a participação de ativos intangíveis de uma empresa em relação ao valor dos ativos tangíveis (Aguiar et al, 2021;Perez & Famá, 2015). Várias pesquisas têm utilizado tal índice para mensurar o NI, sendo relacionados a investimentos, inovações científicas e tecnológicas, e a criação de valor (Medrado et al, 2016).…”
Section: Ativos Intangíveis E Valor De Mercadounclassified
“…Em seu artigo os autores encontraram que alguns aspectos do capital intelectual de fato melhoram a produtividade, e, consequentemente, geram valor para a empresa, porém existem também fatores desse tipo de ativo que não são tão efetivos. Aguiar et al (2021) analisaram a relação entre o uso intensivo de ativos intangíveis e o desempenho econômico das empresas de capital aberto no Brasil. Os resultados mostram que um melhor desempenho dos ativos intangíveis está atrelado ao uso mais intensivo de intangíveis.…”
Section: Ativos Intangíveis E Valor De Mercadounclassified